ANALISIS IMPLEMENTASI KURIKULUM MBKM DI PERGURUAN TINGGI - Lilik Hidayat Pulungan (Hijri, 2023)
This research examines and analyzes the implementation of the Independent Learning-Independent Campus (MBKM) curriculum in tertiary institutions. The method used is descriptive qualitative research method. While the formulation of the research problem is how to implement the MBKM curriculum in tertiary institutions and how the results of the analysis of the MBKM curriculum in tertiary institutions are. As study material that is used as a reference in research are theories, concepts and policies related to Independent Learning. Based on the study material, literature study and analysis results, it was found that the MBKM curriculum in tertiary institutions is needed in the midst of technological advances, and the demands of the industrial world, as well as the global market.Keywords:Curriculum, MBKM, Higher Education